Study of correlation between perinatal outcome, placental coefficient and feto-placental ratio - Sirpurkar, Manik; Anjankar, Vaibhav Prakash; Wankhede, Kanchan; Khanzode, Lata; Jawade, Shashikala (International Journal of Research in Medical Sciences, 2017)
Background: Pregnancy and birth are nature’s finest marvel wherein perfect symbiosis between the two individuals protects the little and weak one and also allows the propagation of genetic prototype of the other individual generation after generation. Placenta acts as a mirror which reflects intrauterine status of fetus. Placenta has an undisputed role in foetal development but still is grossly neglected organ which is equal to liver, lung and kidney in function. Methods: Placentae collected from labor rooms and operation theatres were studied for various parameters like weight, surface area, volume, area of calcification and infarction, number of cotyledons etc. Birth weight of babies was also noted, feto-placental weight ratio and placental coefficient was calculated. Results: Average placental weight being 490.5 gm (range 295-660 gm). Placenta of male baby was found to be slightly heavier as compared to female babies. Birth weight of male babies was also more than female babies. Average placental surface area was found to be 225.5 sq. cm. Mean placental volume was recorded as 450.5 cu. cm. Foeto-placental weight ratio was found to be 5.41:1 irrespective of sex of the baby, 5.61:1 in case of male baby and 5.40:1 for female babies. Conclusion: The placenta is a mirror which reflects intrauterine status of the fetus.